2011
DOI: 10.1373/clinchem.2010.159806
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Serum Visfatin at 11–13 Weeks of Gestation in Gestational Diabetes Mellitus

Abstract: BACKGROUND Visfatin and adiponectin are produced by adipose tissue and have opposite effects on insulin resistance. Circulating concentrations of these biomarkers are altered in type 2 diabetes mellitus. We sought to examine the potential value of maternal serum visfatin and adiponectin concentrations in early pregnancy as potential biomarkers in the prediction of gestational diabetes mellitus (GDM). METHODS This work was a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 31 publications
6
62
0
2
Order By: Relevance
“…Of the 29 potential protein biomarkers, adiponectin is the best studied in relation to GDM [11][12][13][14]16]. Here, adiponectin was the best performing independent predictor of GDM, regardless of BMI grouping.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Of the 29 potential protein biomarkers, adiponectin is the best studied in relation to GDM [11][12][13][14]16]. Here, adiponectin was the best performing independent predictor of GDM, regardless of BMI grouping.…”
Section: Discussionmentioning
confidence: 84%
“…This could be an important tool in future screening strategies to ensure that women at the highest risk undergo a diagnostic OGTT at gestational week 24-28. At present, no serum biomarker with clinical utility has been identified and the potential utility in GDM screening has been investigated for only a limited number of proteins. Adiponectin is by far the best-studied protein biomarker for GDM but lacks the sensitivity and specificity required for clinical use [11][12][13][14][15][16]. Other proteins such as sex hormone binding protein (SHBG), retinol-binding protein 4 (RBP-4), resistin and C-reactive protein (CRP) have also been investigated as potential biomarkers of GDM, but conclusions have been variable [14,[17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Krzyzanowska et al [82] reported markedly higher plasma visfatin concentration in GDM women compared to NGT pregnant controls; however, there was no relationship between visfatin and fasting plasma glucose, plasma insulin, insulin resistance, and BMI. Elevated plasma visfatin concentration in GDM women has also been demonstrated by others [83,84]. Lewandowski et al [83] revealed positive correlations of plasma visfatin levels with concentrations of both fasting and post-glucose-load insulin in GDM women in the third trimester of pregnancy.…”
Section: Visfatinmentioning
confidence: 59%
“…Lewandowski et al [83] revealed positive correlations of plasma visfatin levels with concentrations of both fasting and post-glucose-load insulin in GDM women in the third trimester of pregnancy. Ferreira et al [84] reported an increased plasma visfatin level in the first trimester of pregnancy in women who developed GDM, suggesting that visfatin could be a potential biomarker for predicting GDM. In contrast, a reduced plasma visfatin level, by approx.…”
Section: Visfatinmentioning
confidence: 99%
“…La visfatina está relacionada con el metabolismo de las HDL y existen reportes de su incremento en diabetes gestacional tipo 1 y tipo 2 y obesidad gestacional (17). Adicionalmente, se han encontrado incrementadas las concentraciones de visfatina séricas en el primer trimestre de la gestación en mujeres que desarrollaron preeclampsia por un mecanismo no relacionado a la perfusión placentaria alterada, y en mujeres que presentaron diabetes gestacional (19,20).…”
Section: Tabla I Regulación De Adipocitocinas Durante La Gestación Nounclassified